Patient Complications after Interscalene Block: A Retrospective Comparison of Liposomal Bupivacaine to Nonliposomal Bupivacaine. (27th March 2020) - Hutchins, Jacob L.; Habeck, Jason; Novaczyk, Zac; Campbell, Richard; Creedon, Christopher; Spartz, Ellen; Richter, Michael; Wolter, Jeremy; Suryawanshi, Gaurav; Kaizer, Alexander; Berg, Aaron A.
Abstract : Background . The purpose of this study was to investigate if the addition of liposome bupivacaine (LB) to an interscalene block (ISB) had an effect on the number of patients with surgical- or block-related complications. Methods . This was a single-center retrospective chart view performed by identifying patients who received an ISB from January 1, 2014, through April 26, 2018, at the University of Minnesota. 1, 518 patients were identified who received an ISB (LB = 784, nonliposomal bupivacaine = 734). Patients were divided into two groups those who did receive liposome bupivacaine in their ISB and those who did not receive liposome bupivacaine in their ISB. Medical records were individually reviewed for surgical procedure, block medications, complications related to the block or surgical procedure, phone calls to the healthcare system for issues related to opioids or pain within 3 and within 30 days, readmissions within 30 days, and emergency room visits for complications within 3 and 30 days. Results . There was no significant difference in the number of patients with surgical or anesthetic complications. Only phone calls for pain within 3 days were significantly different. The LB group had 3.2% of patients call compared to 5.6% in the nonliposomal bupivacaine group (aOR = 1.71 (95% CI: 1.04–2.87), p = 0.036 ). We found no significant difference in any of the other secondary outcomes. Conclusions . The use of LB in an ISB demonstrated no significant difference compared to nonliposomal bupivacaine in numbers of complications, emergency room visits, and readmissions.